Periventricular Lesions Help Differentiate Neuromyelitis Optica Spectrum Disorders from Multiple Sclerosis. (9th February 2014) - Raz, Eytan; Loh, John P.; Saba, Luca; Omari, Mirza; Herbert, Joseph; Lui, Yvonne; Kister, Ilya
Abstract : Objective. To compare periventricular lesions in multiple sclerosis (MS) and neuromyelitis optica spectrum disorders (NMOsd). Materials and Methods. Sagittal and axial fluid attenuated inversion recovery (FLAIR) sequences of 20 NMOsd and 40 group frequency-matched MS patients were evaluated by two neuroradiologists. On axial FLAIR, periventricular area was characterized as free of lesions/smooth-bordered ("type A") or jagged-bordered ("type B") pattern. On sagittal FLAIR, the images were evaluated for presence of "Dawson's fingers." Results. Type A pattern was observed in 80% of NMOsd patients by Reader 1 and 85% by Reader 2 but only in 5% MS patients by either Reader. Type B was seen in 15% NMOsd patients by Reader 1 and 20% by Reader 2 and in 95% MS patients by either Reader. Dawson's fingers were observed in no NMOsd patients by Reader 1 and 5% by Reader 2. In MS, Dawson's fingers were seen in 92.5% patients by Reader 1 and 77.5% by Reader 2. The differences in periventricular patterns and Dawson's finger detection between NMOsd and MS were highly significant (P < 0.001 ). Conclusions . Dawson's fingers and "jagged-bordered" periventricular hyperintensities are typical of MS and almost never seen in NMOsd, which suggests a practical method for differentiating the two diseases.